Neurologic manifestations of COVID-19 and viral test in cerebrospinal fluid - Carla de Oliveira Cardoso; Evandra Strazza Rodrigues Sandoval; Lilian Beatriz Moreira de Oliveira Chagas; Soraya Jabur Badra; Dimas Tadeu Covas; Simone Kashima Haddad; Luiz Tadeu Moraes Figueiredo (PLoS ONE, 2025)
Background Neurological manifestations are present in about one-third of COVID-19 cases, ranging from mild symptoms, such as anosmia, to more severe forms like demyelinating syndromes. Although direct invasion of the CNS has been demonstrated, the immune- mediated pathway is also described and more accepted. Even in cases where viral detection in CSF is absent, it should not rule out neuroinvasion. There are few prospective studies about neurological manifestations of COVID-19, especially with viral tests in CSF; as well there are still many questions about COVID-19 associated with neurological disease. Thus, we describe clinical and CSF findings of a prospective cohort of patients with nasal positive tests for SARS-CoV-2 and neurological involvement. We also discuss the pathogenic mechanisms related to these manifestations. Methods and Findings This is a prospective cohort study; 27 patients were evaluated according to clinical presentation, the time interval between COVID-19 diagnosis and onset of neurological alterations, syndromic diagnosis, imaging and CSF findings. Real time polymerase chain reaction for SARS-CoV-2 genome was performed in all CSF samples. 2 RT-PCR in spinal cord fluid resulted positive in 9 (33.3%) cases, five of them had a positive swab nasal test concomitant to neurologic disease. Respiratory signs were described in 12 out 27 patients, five of them with viral detection in CSF. White cell counts in CSF were normal range in the majority of cases, except for 3 occurrences: two patients had elevated CSF WBC counts and viral detection in CSF (10 and 36 cells/mm3) and one also had elevated CSF WBC count but viral detection in CSF was negative (21cells/mm3). The observed neurological signs encompassed a diverse neurologic spectrum, including seizures, paresis, gait abnormalities, headaches, alteration in consciousness and memory or cognitive impairment. Both imaging and CSF alterations exhibited non-specific characteristics. Syndromic diagnoses included stroke, dementia or cognitive impairments, Guillain-Barré Syndrome, encephalitis, encephalomyelitis, acute flaccid palsy and optical neuritis. Conclusions The patients in the present study had COVID-19 and neurologic involvement including a wide range of clinical manifestations. SARS-CoV-2 was detected in one-third of CSF samples, regardless of time interval between COVID-19 diagnosis and the onset of neurological signs. These conditions encompass various pathogenic pathways and the neuroinvasion potential of SARS-CoV-2 should be more studied.